1999
DOI: 10.2337/diacare.22.10.1703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus Calmette-Guerin vaccination on new-onset type 1 diabetes. A randomized clinical study.

Abstract: Vaccination with BCG at the time of onset of type 1 diabetes does not increase the remission rate or preserve beta-cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 0 publications
0
66
0
Order By: Relevance
“…Immunological features. The LEW.1WR1 rat is not lymphopenic; total spleen cell counts (ϫ10 6 ) were 504 Ϯ 80 in LEW.1WR1 rats (n ϭ 3) compared with 300 Ϯ 58 in BBDR rats (n ϭ 3). Table 2 shows the comparative phenotypic profiles of LEW.1WR1, BBDR, and LEW rats at 35-42 days of age.…”
Section: Lew1wr1 Rats and Autoimmune Diabetesmentioning
confidence: 95%
“…Immunological features. The LEW.1WR1 rat is not lymphopenic; total spleen cell counts (ϫ10 6 ) were 504 Ϯ 80 in LEW.1WR1 rats (n ϭ 3) compared with 300 Ϯ 58 in BBDR rats (n ϭ 3). Table 2 shows the comparative phenotypic profiles of LEW.1WR1, BBDR, and LEW rats at 35-42 days of age.…”
Section: Lew1wr1 Rats and Autoimmune Diabetesmentioning
confidence: 95%
“…However, subsequent studies found that early administration of bacille Calmette-Guerin vaccine did not prevent type 1 diabetes. 76,77 Also, the analytical methods used in the Finnish study of Hib vaccine were incorrect, and there were no significant differences in the incidence of type 1 diabetes in Hib-vaccinated infants 10 years later. 78 In addition, 21 421 children who received the Hib conjugate vaccine between 1988 and 1990 in the United States were followed for 10 years and the risk of type 1 diabetes was 0.78 when compared with a group of 22 557 children who did not receive the vaccine.…”
Section: Clinical Studies Evaluating the Relationship Between Vaccinementioning
confidence: 99%
“…Both goals are not easy to achieve using the techniques currently available for patients. Numerous immunological methods have been employed to inhibit autoimmune responses to beta cells in human or animal models of type 1 diabetes [17][18][19][20][21][22][23][24][25][26][27]. However, immunological methods alone were largely unsuccessful in the treatment of clinically overt type 1 diabetes, probably because of the already significantly compromised beta cell mass.…”
Section: Discussionmentioning
confidence: 99%